Needle angle dynamics as a rapid indicator of drought stress in Larix kaempferi (Lamb.) Carrière: advancing non-destructive imaging techniques for resilient seedling production - Jeong, Ukhan; Kim, Dohee; Kim, Sohyun; Han, Seung Hyun; Cheong, Eun Ju (Frontiers in Plant Science, 2025)
Larix kaempferi (Lamb.) Carrière, a valuable species for timber production and reforestation, faces challenges in large-scale seedling propagation due to its slow growth cycle and high susceptibility to environmental stressors. Early detection of drought stress is critical for preparing seedlings for harsh field conditions and for optimizing irrigation strategies. This study aimed to detect drought stress at an early stage in L. kaempferi seedlings by integrating physiological traits with image-based phenotypic measurements, with a focus on needle angle dynamics under controlled drought and irrigation conditions. The apical needle angle of one-year-old seedlings was measured using ImageJ, while seedling-level analysis was conducted using PlantCV to collect data and extract relevant parameters. Statistical analyses were performed to evaluate temporal trends and to identify growth environment and physiological traits significantly influenced by drought stress. As a result, apical needle wilting and recovery, along with seedling-level image analysis (parameter: Center of Mass(y)), exhibited significant responses to drought stress as early as Day 2. This provides a non-destructive method for early detection, preceding observable changes in physiological traits such as chlorophyll fluorescence and needle temperature that responded to drought stress by Day 6, as well as before seedling mortality occurred. Multiple regression analysis indicated that, as drought stress progressed, solar radiation and thermal-related parameters (ФNPQ and needle temperature) emerged as key predictors of needle angle variation. Image-based approaches, including RGB and thermal imaging, proved effective for real-time stress monitoring, demonstrating their practical potential for nursery applications. In summary, this study lays the groundwork for needle-based phenomic approaches using imaging techniques in nursery systems and highlights the need for further research to optimize these methods for the large-scale, cost-effective production of high-quality, drought-resilient L. kaempferi seedlings.